AB1217 Methotrexate and low incidence of uveitis in children suffering from persistend or extended oligoarthriitis. (23rd January 2014) - Emminger, W.; Fodor, S.; Pichler, G.; Ulbrich, A.; Funk, M.; Barisani, T.
Abstract : Background: The incidence of uveitis in children suffering from persistent or extended oligoarthritis has been shown to be about 17 to 32%. Uveitis and its local corticosteroid (CS) therapy are associated with a high rate of acute and chronic ocular complications and are responsible for a significant morbidity in children and in adulthood. Methods: We retrospectively analysed all consecutively treated children of a single pediatric rheumatology outpatient clinic, who were receiving weekly methotrexate (MTX) for therapy of oligoarthritis during the time period from January 2002 to November 2011. In order to study a population which is at a high risk to develop uveitis, inclusion criteria were as follows: age below seven years at the first episode of oligoarthritis and an observation time period of at least 6 months. Exclusion criteria were: other types of juvenile idiopathic arthritis (JIA) and a diagnosis of uveitis before the onset of oligoarthritis. The children underwent slit lamp examinations at regular intervals, most of them were examined at the department of ophthalmology of the Medical University of Vienna. Results: 30 children, 24 girls and 6 boys, fulfilled the inclusion criteria, 29 of them were positive for antinuclear antibodies. The age at the start of arthritis was median 2 7/12 years (1 3/12- 6 6/12).The time duration from the onset of arthritis to the start of MTX therapy was median 4 months (2-30 months). The median duration of MTX therapy was 30 months (8-77). The median observation time after start of oligoarthritis was 47, 5 months (24-106). During continuing MTX therapy, only one of 30 children had a diagnosis of uveitis and this was diagnosed just 3 months after the start of MTX therapy. In one other child, a first episode of an anterior uveitis was diagnosed 3 months after MTX had been stopped after tapering it. Conclusions: In this retrospective analysis the observation time after the diagnosis of oligoarthritis was long with median 47, 5 months (24-106). MTX therapy was associated with a very low incidence of uveitis in children suffering from persistent or extended oligoarthritis. Uveitis is associated with a high rate of acute and late complications due to the disease and due to topical CS therapy. The significant morbidity due to late ocular complications may be reduced in those children, who are receiving MTX for therapy of persistent or extended oligorarthritis. Disclosure of Interest: None Declared